Optimization of Fermentable Sugar Production from Pineapple Leaf Waste (Ananas comosus [L.] Merr) by Enzymatic Hydrolysis - Yohanita Restu Widihastuty; Sutini Sutini; Aida Nur Ramadhani (Universitas Diponegoro, 2021)
Pineapple leaf waste is one agricultural waste that has high cellulose content. Pineapple leaf waste's complex structure contains a bundle of packed fiber that makes it hard to remove lignin and hemicellulose structure, so challenging to produce reducing sugar. Dried pineapple leaf waste pretreated with a grinder to break its complex structure. Delignification process using 2% w/v NaOH solution at 87oC for 60 minutes has been carried out to remove lignin and hemicellulose structure so reducing sugar could be produced. Delignified pineapple leaf waste has been enzymatic hydrolyzed using cellulase enzyme (6 mL, 7 mL, and 8 mL) to produce reducing sugar. The sample was incubated in an incubator shaker at 155 rpm at 45, 55, and 60oC for 72 hours. Determination of reducing sugar yield had been carried out using the Dubois method and HPLC. The model indicated that the optimum operating condition of enzymatic hydrolysis is 7 mL of cellulase enzyme at 55oC to produce 96,673 mg/L reducing sugar. This result indicated that the enzymatic hydrolysis operating condition improved the reducing sugar yield from pineapple leaf waste. The optimum reducing sugar yield can produce biofuel by the saccharification process.